Characterizing Black Carbon and Gaseous Pollutants on the Yangtze River Across Eastern China Continent. Issue 8 (14th April 2021) - Ting, Y.; Liu, D.; Morgan, W. T.; Allan, J. D.; Coe, H.; Li, C.; Wang, X.; Ye, X.; Chen, J.
Abstract: The Yangtze River (YR) region and cities along the river have severe deterioration of air quality due to urbanization and economic development. Black carbon (BC) has significant impacts on air quality and climate, however it is poorly characterized across the region. Here we report the first continuous measurements of BC and gaseous pollutants along the YR in wintertime, with an intensive observation period from November 21 to December 4, 2015, covering ∼7° longitude over the continent in China. The highly polluted periods (HPP) with NO x  >80 μg m −3 indicated more localized emissions. At the western (longitude <118°E) and eastern (longitude >118°E) ends of the YR valley, the HPP events reduced, mostly since the western end was influenced by terrain height and regional transport, and the eastern end was influenced by easterly oceanic or westerly continental air masses. In these regions, BC core size decreased by 5%–19% during the HPP, and had modes of mass median diameter in the range 120 –180 nm, which was found to be predominately from local sources, contrasting with a more consistent mode ∼200 nm that was due to BC from mixed sources. A comparison of simultaneously measured data from the nearby monitoring stations along the river demonstrated a high consistency of PM2.5 over the river, which reflected the important regional impact on the particulate mass. This study evaluates the shipping emission and regional influence over the YR and may guide the policy maker on mitigating air pollution. Key Points: The first continuous measurements of black carbon (BC) and gaseous pollutants along the Yangtze River were conducted in wintertime covering ∼7° longitude over the continent in China BC core size decreased by 5%–19% during the highly polluted periods, and had modes of mass median diameter in the range 120 –180 nm, which was found to be predominately from local sources, contrasting with a more consistent mode ∼200 nm that was due to BC from mixed sources The evaluation of the shipping emission and regional influence over the Yangtze River can underpin the mitigation strategies of air pollution